A enfermagem na linha de frente: indicadores de mortalidade destes profissionais durante a pandemia de Covid-19 - Ferreira, Fatima Dayanne Wirtzbiki (2023)
SARS-CoV-2 or new coronavirus is responsible for the development of COVID-19 in humans, a public health problem that has been plaguing the entire worldpopulation since then. Due to the exponential increase in cases, on March 11, 2020, the World Health Organization (WHO) declared the situation a pandemic. In Brazil, finding cases among professionals is one of the biggest concerns of the Unified HealthSystem (SUS). As nursing is a very expressive professional category in all health services, it has become the focus of monitoring and case identification through the creation of an online portal by the Federal Nursing Council (COFEN). The study aimedto characterize the pattern of mortality from COVID-19 in nursing professionals duringthe COVID-19 pandemic in Brazil from 2020 to 2022. A descriptive and ecological cross-sectional epidemiological study with spatial analysis of deaths from COVID-19 in nursing professionals, based on access to secondary data, notified and available ina database made available by the Cofen portal (http://observatoriodaenfermagem.cofen.gov.br/). A descriptive analysis was carried out on data from cases of COVID-19 reported to nursing professionals in Brazil, from March 2020 to December 2022. The first case of death registered in Brazil was on 03/20/2020, nursing technician category , in the municipality of Sergipe. From the first notification of death in the category until December 2022, 30,857 confirmed cases of COVID-19 were registered in nursing professionals, of which 833 evolved to death, resulting in a lethality of 2.69% of the study population. Regarding the number of deaths by professional category, there were a total of 245 (29.41%) nurses, 478 (57.38%) nursing technicians and 110 (13.20%) nursing assistants. Most deaths wereregistered in females (567; 68.06%) and in the age group between 41 and 60 years (492; 59.06%). The high mortality rates in nursing professionals are explained by someauthors, prioritizing the vulnerable working conditions of Nursing professionals, culminating in illness and death. The sudden drop that we identified in mortality in thethree-year period analyzed in the study is notorious. The total number of deaths of nursing professionals in 2020 was 434, in 2021 it was 398, and in 2022 only a single death was recorded. They faced long hours at work, emotional and physical exhaustion, and yetthey remained steadfast in their commitment to caring for patients. Exhausting workloads, insufficient wages, lack of material resources and fear of contamination, surrounded the routine of professionals who remained on the front line. It is essential that society, health institutions and 5 governments unite to promote the appreciation of nursing professionals, guaranteeing them the appropriate conditions to carry out theirwork in a dignified, safe, effective and respectful manner